2018
DOI: 10.3346/jkms.2018.33.e166
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Endoscopic Screening Interval for Early Detection of Gastric Cancer: a Single-Center Study

Abstract: BackgroundThe optimal endoscopic screening interval for early gastric cancer (EGC) detection still remains controversial. Thus, we performed this prospective study to clarify the optimal interval between endoscopic examinations for EGC detection.MethodsA questionnaire survey for penultimate endoscopy and gastric cancer (GC) diagnosis interval was used; the findings were then analyzed. The patients were divided into two groups according to GC type and endoscopic examinations intervals.ResultsA total of 843 pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 24 publications
(39 reference statements)
4
10
0
Order By: Relevance
“…There was a significant dose-response relationship between surveillance interval and the rate of curative endoscopic resection. These results are similar to that of another Korean study published recently, which showed that triennial endoscopic screening might be as effective as biennial screening in detection of early gastric cancer and subsequent curative endoscopic resection rate [ 4 ]. Another study raised the issue of patients with a high risk of gastric cancer, such as those with intestinal metaplasia, and insisted that screening at 1-year interval would be beneficial in such cases [ 5 ].…”
supporting
confidence: 90%
“…There was a significant dose-response relationship between surveillance interval and the rate of curative endoscopic resection. These results are similar to that of another Korean study published recently, which showed that triennial endoscopic screening might be as effective as biennial screening in detection of early gastric cancer and subsequent curative endoscopic resection rate [ 4 ]. Another study raised the issue of patients with a high risk of gastric cancer, such as those with intestinal metaplasia, and insisted that screening at 1-year interval would be beneficial in such cases [ 5 ].…”
supporting
confidence: 90%
“…Currently, there is no national screening program for GC in Vietnam, and some hospitals designed their own surveillance schedules. Recent studies reported that a surveillance interval of every two years would be ideal to detect GC in the early stages [14,15], but the crucial issue would be the quality of the index EGD endoscopic examination as well as the endoscopist's experience in recognizing [16]. This is an important issue which should be further investigated in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…Heterotopic xenograft mice model 1 × 10 7 GCCs were transplanted into the proximal thigh region of BALB/c nude mice (male), and we observed the model until the tumor volume expanded up to 4000 mm 3 . Implanted tumor size was assessed three times per week and calculated by (4/3) × π × (minor axis/ 2) 2 × (major axis/2) mm 3 . Tumorigenicity was measured in the third week after injecting the cells (n = 10 per group).…”
Section: Orthotopic Mice Modelmentioning
confidence: 99%
“…And the incidence of GCA is profound in South Korea, Mongolia, China, and Japan [1]. Even though early detection of the tumor can prolong the survival of patients [2,3], about 33% of patients with gastric cancer (GCA) are diagnosed with diffuse GCA (DGCA) [4]. As the name implies, DGCA infiltrates the contour of the stomach insidiously, which lead to the incomplete resections.…”
Section: Introductionmentioning
confidence: 99%